Teacher education in Trinidad and Tobago: Costs, financing and future policy - Lewin, Keith M.; Keller, Carol (Centre for International Education, University of Sussex Institute of Education, 2000)
The first section of this paper outlines general characteristics of the education system in Trinidad and Tobago and its financing. The second section draws attention to recent developments that will shape the future of teacher education, and the third section presents the detailed profile of current provision for training primary teachers through the two teacher education colleges and the University of the West Indies (UWI). Data is provided on enrolments and output, and curriculum organization. In the fourth section, cost and finance are considered in order to assess the cost of producing trained primary teacher, while the fifth section develops projections of future demand and identifies how demand will change under different assumptions. The last section consolidates the analysis and explores the range of policy options that may be considered. It is observed that teacher education is currently hampered by lack of investment in infrastructure, a lack of linkage between the on the job (OJT) training programme and other parts of teacher education, an overloaded curriculum, and an anomalous salary scale whereby teacher educators are paid the same as secondary school teachers. It is noted that as demand for primary school teachers in Trinidad and Tobago is likely to fall in coming years, there is a window of opportunity to revisit the teacher education curriculum, for instance in terms of balance between teaching and assessment, the possible provision of more in-service by college staff, and clearer links.
MUSTER (Multi-Site Teacher Education Research Project)
Keywords: Muster project; teacher education